Essere insegnanti con una formazione antropologica. Una riflessione su “seconde generazioni” e disuguaglianze nella Scuola Secondaria di Primo Grado - Gentile, Giada (Antropologia Pubblica, 2025)
The report aims to share and summarize the reflections developed during the years of work in the educational sector, from 2016 to today, lived as a person with an anthropological training, first as an after-school operator and then as a teacher. The geographical context is the western area of the Friuli Venezia Giulia Region, in the Northeast of Italy, in the former Province of Pordenone. By an experience within 13 classes in seven different middle schools, the condition of the “second generation” kids is addressed, related to power imbalances, self-identification and to the topic of citizenship, especially in the context of the teaching of Civic Education.